القضايا اللغوية في" أوجز المسالك إلى موطأ مالك " لمحمد زكريا الكاندهلوي قضية المرفوعات النحوية "الفاعل" أنموذجا (Khairulummah, 2022)
This research paper is based on Explanation of sayings of Prophet Muhammad (S.A.W.W). The book of Hadith known as “Muata Imam Malik”. That was the first chapter wise arranged book of Hadith in the History of Hadith, after that other books has been compiled. The book “Muata Imam Malik” has been explained many times due to its importance and authenticity in Hadith and many explanations have been written all over the Islamic world. Al-Shaikh Zakirya has written its explanation in Sub-continent and commented on different matters. The main focus of this research paper on the Linguistics matters which includes: Phonetics, Morphological, Syntactical and semantic issues of Arabic Language. I have taken only one issue that is related to the “Subjective” status of a word i.e. “فاعل” the Subject in a verbal sentence. After highlighting these linguistic issues one can know the level of knowledge of this eminent scholar of Islam in general and of Sub-continent in special.